68Ga labeled fatty acids for cardiac metabolic imaging: Influence of different bifunctional chelators. Issue 23 (1st December 2016) - Jain, Akanksha; Mathur, Anupam; Pandey, Usha; Sarma, Haladhar Dev; Dash, Ashutosh
Graphical abstract: Abstract: Development of 68 Ga labeled fatty acids is of immense interest due to the availability of 68 Ga through a generator and its superiority over SPECT based tracers in carrying out dynamic imaging on a PET scanner. Our present work explores the influence of different chelators on the cardiac uptake and pharmacokinetics of the 68 Ga-labeled fatty acids. Two new 68 Ga labeled fatty acids were synthesized by conjugation of 11-aminoundecanoic acid with the bifunctional chelators (BFCs) viz. p -SCN-Bn-DTPA ( S -2-(4-isothiocyanatobenzyl)-diethylenetriaminepentaacetic acid) and p -SCN-Bn-NODAGA ( S -2-(4-isothiocyanatobenzyl)-1, 4, 7-triazacyclononane-1-glutaric acid-4, 7-acetic acid) and their comparison was carried out with the previously reported 68 Ga–NOTA–undecanoic acid. Both the conjugates were radiolabeled with 68 Ga in high yields and purities (>95%). Their formation was established by preparation and characterization of their inactive analogs with nat Ga at macroscopic levels. Biodistribution studies of the complexes in Swiss mice showed lower initial myocardial uptake for 68 Ga–NODAGA–undecanoic acid (3.8 ± 0.6% ID/g) and 68 Ga–DTPA–undecanoic acid (1.3 ± 0.5% ID/g) complexes in comparison to previously reported 68 Ga–NOTA–undecanoic acid complex (7.4 ± 2.8% ID/g) at 2 min p.i. However, significant retention of the tracer in the myocardium was observed in the case of 68 Ga–NODAGA–undecanoic complex, which led to improved heart/non-target ratios of the complex over time in comparison to the other 68 Ga complexes. Similarly, the DTPA complex exhibited increased washout from the liver in comparison to other 68 Ga derivatives. The β oxidation mechanism in myocytes was investigated by isolating the myocardial extract post intravenous injection of the respective 68 Ga complexes and analyzing them by radio-HPLC, which showed metabolic transformation of the parent fatty acid complex peak in all the three complexes. This study has provided an insight into the design characteristics of 68 Ga labeled fatty acids to achieve the desired myocardial imaging characteristics.